Innovative Leadership in the Perspective of the Qur'an and Modern Management (Analysis of Leadership Styles, Communication Strategies, and Innovative and Sustainable Organizational Culture) - Supriatna, Papay (Review: Journal of Multidisciplinary in Social Sciences, 2025)
In the era of globalization and technological development, Islamic education faces major challenges in maintaining Islamic values ​​while adapting to modern managerial strategies. This study aims to analyze the concept of Islamic leadership based on the principles of justice, exemplary, trustworthy, and deliberation, and to compare it with innovative leadership models in modern management. The method used is qualitative research with a literature study approach (library research). Data were obtained from various academic sources, including interpretations of the Qur'an, hadith, and Islamic and modern leadership theories. Content analysis techniques were applied to interpret the meaning of leadership based on Islamic moral principles and their relevance in organizational management. The results of the study indicate that leadership in Islam emphasizes moral and spiritual values, which play an important role in building organizational integrity, trust, and effectiveness. The principle of justice (al-adl) contributes to transparent and ethical decision-making, while exemplary (uswatun hasanah) is key to building a positive work culture. Trustworthy in leadership encourages accountability and responsibility, while deliberation strengthens collective participation in decision-making. Compared to the transformational and innovative leadership models in modern management, Islamic leadership has advantages in the integration of spiritual values ​​with sustainability-oriented leadership practices.